Agribusiness Indicators : Kenya - World Bank (Washington, DC, 2014)
The importance of agriculture in the economies of sub-Saharan African countries cannot be overemphasized. With agriculture accounting for about 65 percent of the region's employment and 75 percent of its domestic trade, significant progress in reducing hunger and poverty across the region depends on the development and transformation of the agricultural sector. Transforming agriculture from largely a subsistence enterprise to a profitable commercial venture is the prerequisite and driving force for accelerated development and sustainable economic growth in sub-Saharan Africa. The rationale behind the development of agribusiness indicators (ABIs) is to construct indicators for specific factors to support successful, effective private sector involvement in agriculture. The indicators can be used to benchmark and monitor performance in the agricultural sector over time and across countries. The resulting information can provoke knowledge flows and meaningful dialogue among policy makers, government officials, donors, private sector actors, as well as other stakeholders in the agricultural sector. This study is predicated on the fact that agriculture is the backbone of the economies of most countries in sub-Saharan Africa, including Kenya. The ultimate aim is to stimulate debate and dialogue among policy makers in specific African countries to engender change and reform in areas where investment is needed to leverage agribusiness and economic development. This study relied heavily on an extensive secondary data collection and literature review, supplemented by informal surveys to solicit information from a broad spectrum of stakeholders and actors in Kenya's agricultural sector. The review and interviews focused on the factors that the agribusiness indicators team determined to be the most critical for agribusiness development across sub-Saharan Africa, based on extensive scoping missions in three pilot countries (Ghana, Ethiopia, and Mozambique). This report is organized into following chapters: chapter one gives introduction; chapter two presents ABI methodology; chapter three presents findings on the success factors and indicators; and chapter four gives concluding remarks.